MYTHOLOGEME OF "EARTHLY PARADISE" IN SLAVIC BELIEFS - Матюхина, А. А. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
The article is devoted to the mythologeme of "earthly paradise", the process of its changes in beliefs of the Slavic people.